Social skills and relationships in Turner syndrome. Issue 2 (March 2019) - Wolstencroft, Jeanne; Skuse, David
Abstract : Purpose of review: Summarize the literature on the social skills and relationships of women with Turner syndrome and examine the biological and psychological factors that may contribute to social interaction difficulties. Recent findings: Turner syndrome is often associated with impaired social–cognitive processing and executive function deficits. These cognitive abnormalities, together with a range of physical differences, may adversely affect social communication skills, which typically begin to impair quality of life during early adolescence. Parental accounts of their daughter's social skills frequently highlight interaction problems, both in the home and beyond; in contrast, self-reports are usually far more positive. At present, we do not know the extent to which such self-reports reflect a lack of social awareness, or a lack of concern about social difficulties. Summary: Women with Turner syndrome are likely to experience social interaction challenges (especially in friendships and relationships) across the lifespan. Providing appropriate guidance and support to them demands a better understanding of their strengths and weaknesses.